Online Integrated Platform for Project Management - J., Sathya Priya; V., Murugavel; S., Viswanathan (Journal of Ubiquitous Computing and Communication Technologies, 2024)
The Integrated Platform for University Projects (IPUP) aims to streamline student project management across academic disciplines. Utilizing web technologies and project management principles, IPUP provides a centralized hub for collaboration, communication, and progress tracking. Additionally, IPUP utilizes a plagiarism checking API as a method to ensure academic integrity. Project documentation submitted on the platform is analysed using the SmallSEO Tools Plagiarism checking API. This API employs algorithms defined by SmallSEO Tools to detect any plagiarized content within the documentation. The API returns a response indicating the percentage of content identified as copied. A predetermined threshold is set for this percentage; if the value exceeds this threshold, the submission is rejected by the website. IPUP serves as a driving force for academic innovation, enabling cross-disciplinary learning and excellence in project-based education, while also integrating communication tools and prioritizing data security.
Keywords: Integrated Platform; University Projects; Collaboration; Project Management; Communication; Transparency; Plagiarism; Efficiency; Data Security; Privacy